2020
DOI: 10.3389/fpsyg.2020.610856
|View full text |Cite
|
Sign up to set email alerts
|

“Time for Recovery” or “Utter Uncertainty”? The Postponement of the Tokyo 2020 Olympic Games Through the Eyes of Olympic Athletes and Coaches. A Qualitative Study

Abstract: The current COVID-19 pandemic has affected the entire globe, including the world of high-performance sports. Accordingly, it has been widely assumed that the thereby caused postponement of the Tokyo 2020 Olympic Games could have negative psychological impacts for aspirants, since they were halted abruptly in the pursuit of their Olympic endeavors and their daily lives drastically altered. Considering the sudden nature of the pandemic, few researchers, if any, have yet scrutinized the individual experience of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 70 publications
3
27
0
Order By: Relevance
“…Considering how much psychosocial factors contribute to DE development, COVID-19 is anticipated to have generated significant changes to athletes food-body relationship especially given the closure of gyms and training facilities, reduced access to healthcare provision including injury rehabilitation and management, limited team access including the central role of teammates and coaches, and the cancellation of competitions [37][38][39][40][41]. The postponement of the 2020 Tokyo Olympics is of particular note for elite athletes as it is an event that individuals commit many years towards whereby the psychosocial preparation towards the event is significant and psychological distress has been anticipated in those this postponement has affected [37,[42][43][44]. Typically, in moments of stress, athletes have been seen to enlist in additional social support, utilise cohesive training environments and direct attention to their training and competition goals [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…Considering how much psychosocial factors contribute to DE development, COVID-19 is anticipated to have generated significant changes to athletes food-body relationship especially given the closure of gyms and training facilities, reduced access to healthcare provision including injury rehabilitation and management, limited team access including the central role of teammates and coaches, and the cancellation of competitions [37][38][39][40][41]. The postponement of the 2020 Tokyo Olympics is of particular note for elite athletes as it is an event that individuals commit many years towards whereby the psychosocial preparation towards the event is significant and psychological distress has been anticipated in those this postponement has affected [37,[42][43][44]. Typically, in moments of stress, athletes have been seen to enlist in additional social support, utilise cohesive training environments and direct attention to their training and competition goals [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…Athletes experience high psychological and physiological stress during their career, especially in competitive periods (Kellmann and Günther, 2000;Steinacker et al, 2000;Oblinger-Peters and Krenn, 2020). In detail, Steinacker and colleagues reported decreases of performance, gonadal and hypothalamic steroid hormones, and deterioration of psychological recovery during very high load training in elite rowers, thereby highlighting the interaction between mood state and metabolic stress (Steinacker et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we see in the current study that Polish athletes, especially women, have a stronger response to the lockdown situation, which should receive particular interest. Numerous studies show that athletes all around the world experienced a decrease in mental wellbeing, an increased level of stress, anxiety, depressive symptoms and feelings of anger, confusion during the first lockdown, and women and individual sports representatives seem to have the highest costs of the problematic situation of pandemic [1,9,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The Spanish athletes followed the rules and decisions on quarantine and agreed to Olympics cancellation comparing to Polish athletes. Following Oblinger-Peters and Krenn [21], Olympic sportspeople will presumably face the global health crisis because of their attitude toward the Olympic games as a symbol of lifelong dreams and visions and cultivation or culmination of their professional sports goals. Adaptation to the situation seems crucial, and the current study showed that Spanish athletes adjusted to the confinement situation better than Polish respondents.…”
Section: Discussionmentioning
confidence: 99%